A Moderating Role of Green Practices on the Relationship between Service Quality and Customer Satisfaction: Chinese Hotel Context. Issue 1 (2nd January 2018) - Lee, Seoki; Sun, Kyung-A; Wu, Luorong (Laurie); Xiao, Qu
ABSTRACT: The purpose of the current study is to investigate the existence of a moderating effect of a green initiative on the relationship between service quality and customers' satisfaction in the Chinese hotel context. The study adopts a 2 × 2 between-subjects experimental design using scenarios. Four scenarios provide a mixed combination of high or low cases for a hotel's green participation, and good or poor cases for service quality. The study uses the survey method to collect data from Chinese guests. It finds the main effect of service quality on customers' satisfaction and a significant moderating role for green initiatives on the relationship between service quality and customers' satisfaction, but interestingly found an opposite direction of the moderating role to the one hypothesized. The study's results also reveal an insignificant main effect of a green initiative on customers' satisfaction. The study provides theoretical and practical implications.